2019
DOI: 10.1097/nor.0000000000000608
|View full text |Cite
|
Sign up to set email alerts
|

The Journey Toward Taking the Day for Granted Again

Abstract: BACKGROUND: A hip fracture is an unexpected, subjective, traumatic experience that affects the person in both physical and emotional ways. PURPOSE: The purpose of this study was to describe rural older people's experiences of recovering after hip fracture surgery. METHODS: Thirteen individual interviews were conducted with older people. The interview texts were analyzed with qualitative content analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
(44 reference statements)
5
5
0
Order By: Relevance
“…A qualitative systematic review (26) also found that nurses played a signi cant role in coordinating between different health care settings, and post-discharge intervention was necessary for facilitating safe discharge transition. The current nding that some older adults struggled to recover functions such as exercising and eating was consistent with a previous study (19), which reported that older adults began to plan for their recovery immediately after hip fracture surgery because regaining independence was the most important issue in their daily life (19).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A qualitative systematic review (26) also found that nurses played a signi cant role in coordinating between different health care settings, and post-discharge intervention was necessary for facilitating safe discharge transition. The current nding that some older adults struggled to recover functions such as exercising and eating was consistent with a previous study (19), which reported that older adults began to plan for their recovery immediately after hip fracture surgery because regaining independence was the most important issue in their daily life (19).…”
Section: Discussionsupporting
confidence: 91%
“…The third theme, dependent compliance includes absolute trust in healthcare providers, indispensable support from the family, and passive participation in care. The result regarding absolute trust in healthcare providers was similar to a previous study (19) in which older adults expressed their need to feel supported by healthcare providers. Older adults also depended entirely on family members, likely because of the family-centered culture (39) and limited social interaction (4), although some had home-visit care services during limited hours in their home.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Hip fractures require particularly long periods to recover, and dependence is inevitable during a discharge transition [ 12 ]. The major transitional difficulties that older adults face after hip fractures are physical function limitations, and pain and its management [ 13 ].…”
Section: Introductionmentioning
confidence: 99%